Phylogenetic study of the botryosphaeriaceae species associated with avocaodo and pará rubber in Thailand - Thippawan Trakunyingcharoen (2018)
© 2015 Chiang Mai University. All rights reserved. Species of fungi in the family Botryosphaeriaceae have a cosmopolitan distribution with a wide range of plant hosts and several species are associated with cankers, decline, dieback and rot diseases. This study considered the taxonomy of this group of fungi associated with avocado (Persea americana; Lauraceae) and Par rubber (Hevea brasiliensis; Euphorbiaceae) from Thailand based on the combination of morphological characteristics and phylogenetic inference. Taken together, the pathogenicity was determined on avocado fruits and avocado and Pará rubber trees. Phylogenetic inference revealed that species of Botryosphaeriaceae included Lasiodiplodia pseudotheobromae from avocado, and Pseudofusicoccum adansoniae and L. pseudotheobromae from Pará rubber. To our knowledge, this study represents the first report of L. pseudotheobromae associated with avocado, and P. adansoniae and L. pseudotheobromae associated with Par rubber trees in Thailand. Pathogenicity tests indicated that L. pseudotheobromae caused stem-end and midsection rot of avocado fruit and produced canker on both avocado and Par rubber trees exhibiting brown necrotic lesions on inoculated stems. Lasiodiplodia pseudotheobromae was more virulent than P. adansoniae on Par rubber trees and produced more severe canker symptoms.